David Spriggs: Archaeology of Space - Spriggs, David (Southern Alberta Art Gallery; Rodman Hall Arts Centre, 2008)
Exhibition catalog. May-Sep 2008 @Rodman Hall Arts Centre, Jan-March 2008 @ Ontario and Southern Alberta Art Gallery.
English
Keywords: N4390-5098 Visual Arts- Exhibitions